UPAYA PENGINTEGRASIAN NILAI-NILAI ISLAM DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SEKOLAH DASAR - Sabanil, Syahrul; Sulistyowati, Sulistyowati; Nuraeni, Heni Ani (LPPM UM Metro, 2024)
AbstractIn the context of education in Indonesia, integrating religious values, especially Islam, in learning, one of which is Pancasila education learning, has an important role in the development of a complete human being from all sides, one of which is the development of positive character to form students who have responsibility, good morals, and respect cultural and social values. The reason for conducting this research is to describe the efforts made by educators in combining Islamic values in Pancasila learning especially in class V of SDN Pekayon 16 Pagi. This study uses qualitative research with descriptive methods. The technique for collecting this data uses observation, interviews, and documentation. The data analysis technique used in this study uses an interactive model according to Miles and Huberman consisting of collecting data, reducing data, presenting data, and conclusions or verifying data. The results of the study showed that teachers at SDN Pekayon 16 Pagi had maximized the integration of Islamic values in learning, especially Pancasila Education, where the efforts made were to connect all the precepts of Pancasila with religious teachings, especially Islam, then linked to relevant experiences of students' daily lives and the use of various teaching methods such as contextual approaches, habituation to apply all Pancasila and Islamic values in life, and the use of lecture and group methods. The challenges faced, such as religious diversity, culture, and student understanding can be overcome.Keywords: Islamic values, Learning, Pancasila education